Lactational High Fat Diet in Mice Causes Insulin Resistance and NAFLD in Male Offspring Which Is Partially Rescued by Maternal Metformin Treatment - Hafner, Hannah; Mulcahy, Molly C.; Carlson, Zach; Hartley, Phillip; Sun, Haijing; Westerhoff, Maria; Qi, Nathan; Bridges, Dave; Gregg, Brigid (Frontiers in Nutrition, 2021)
Maternal metabolic disease and diet during pregnancy and lactation have important implications for programming of offspring metabolic disease. In addition, high fat diets during pregnancy and lactation can predispose offspring to non-alcoholic fatty liver disease (NAFLD), a rising health threat in the U.S. We developed a model of maternal obesogenic high fat feeding exclusively during the lactation period. We previously showed that offspring from dams given lactational high fat diet (HFD) are predisposed to obesity, glucose intolerance and inflammation. In separate experiments we also showed that lactational metformin treatment can decrease offspring metabolic risk. The purpose of these studies was to understand the programming implications of lactational HFD on offspring metabolic liver disease risk. Dams were fed a 60% lard-based HFD from the day of delivery through the 21 day lactation period. A subset of dams were also given metformin as a co-treatment. Starting at weaning offspring were fed normal fat diet until 3 months of age at which point a subset were challenged with an additional HFD stressor. Lactational HFD fed male offspring developed hepatic insulin resistance. Postweaning HFD challenge led male offspring progressing to NAFLD with more severe outcomes in the lactational HFD challenged offspring. Co-administration of metformin to lactating dams on HFD partially rescued the offspring liver metabolic defects in males. Lactational HFD or post weaning HFD had no impact on female offspring with them maintaining normal insulin sensitivity and liver phenotype. These findings indicate that HFD diet during the lactation period programs adult offspring NAFLD risk in a sexually-dimorphic manner. In addition, early life intervention with metformin via maternal exposure may prevent some of the liver programming caused by maternal HFD.